2015
DOI: 10.1038/srep16692
|View full text |Cite
|
Sign up to set email alerts
|

Obesity rates in two generations of Swedish women entering pregnancy and associated obesity risk among adult daughters

Abstract: We examined changes in obesity rates in two generations of Swedish women entering pregnancy, and assessed the effects of maternal body mass index (BMI) on the risk of overweight or obesity among adult daughters. This study covered an intergenerational retrospective cohort of 26,561 Swedish mothers and their 26,561 first-born daughters. There was a 4-fold increase in obesity rates, which rose from 3.1% among women entering pregnancy in 1982–1988 to 12.3% among their daughters in 2000–2008 (p < 0.0001) when ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Perhaps the most influential human studies have been on the Dutch famine, clearly demonstrating that men and women conceived during the Dutch Hunger Winter in 1944-1945 who had been exposed to the famine during the first half of pregnancy had higher rates of obesity in adulthood [8,9]. However, food shortages are currently not a persistent problem in industrialized countries, where an ever-increasing number of women enter pregnancy overweight or obesity [10,11]. While research on maternal health behaviors during pregnancy and offspring health outcomes is still in its infancy, the findings so far suggest that a higher maternal pre-pregnancy body mass index (BMI) [12], excess gestational weight gain [12], gestational diabetes mellitus [13], and an unhealthy maternal lifestyle before pregnancy [14] increase the long-term risk of overweight and obesity in their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most influential human studies have been on the Dutch famine, clearly demonstrating that men and women conceived during the Dutch Hunger Winter in 1944-1945 who had been exposed to the famine during the first half of pregnancy had higher rates of obesity in adulthood [8,9]. However, food shortages are currently not a persistent problem in industrialized countries, where an ever-increasing number of women enter pregnancy overweight or obesity [10,11]. While research on maternal health behaviors during pregnancy and offspring health outcomes is still in its infancy, the findings so far suggest that a higher maternal pre-pregnancy body mass index (BMI) [12], excess gestational weight gain [12], gestational diabetes mellitus [13], and an unhealthy maternal lifestyle before pregnancy [14] increase the long-term risk of overweight and obesity in their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…The Developmental Origins of Health and Disease (DOHaD) hypothesis, now substantiated by extensive animal and human research, suggests that both maternal nutrient deficiency as well as nutrient excess in utero and in early infancy results in an acquired susceptibility to metabolic disease later in life (1,2) and across generations (3). Maternal obesity increases the risk for pediatric obesity and impacts multiple organs and metabolic systems underlying a broad array of chronic illnesses -including diabetes, nonalcoholic fatty liver disease, and cardiovascular disease -that are becoming increasingly common at younger ages (4).…”
Section: Introductionmentioning
confidence: 99%
“…Catalano et al showed that the offspring of obese mothers had increased body fat, higher levels of inflammation and greater insulin resistance at birth than offspring born of lean women. Later in life, first‐born daughters born of obese women have risk of developing adult obesity that is nearly 5 times higher than those born to lean women …”
Section: Discussionmentioning
confidence: 99%